DESIGN AND IMPLEMENTATION OF AN INCUBATOR AGROINDUSTRIALES OF BUSINESS - Inche M., Jorge (2002)
The present work deals with the design of a physical facility, the technical and economic aspects for the implementation of a business incubator within the Faculty of Industrial Engineering which could house a small agricultural?industrial business, and therefore be able to access the resources and links needed for the business growth ad development.